Essentials of medical biochemistry with clinical cases - Ha, Chung Eun; Bhagavan, N.V (Academic Press, 2022)
"Essentials of Medical Biochemistry, Third Edition offers a condensed, yet detailed overview of clinical biochemistry, spanning fundamentals and relevant physiologic and pathophysiologic concepts. Pivotal clinical case studies aid in understanding basic science in the context of diagnosis and treatment of human diseases, and the text illuminates key topics in molecular immunology and hemostasis. Users will find fundamental concepts aiding students and professionals in biochemistry, medicine, and other healthcare disciplines. The text is a useful refresher that will help users meet USMLE and other professional licensing examination requirements, providing thorough introductions, key points, multicolored illustrations of chemical structures and figures, fact-filled tables, and recommended reading lists. This Third Edition has been fully updated to address evolving techniques in the biological sciences, including genomics, metabolomics, transcriptomics, epigenomics, proteomics, and gene therapy, among other methods. In addition, each chapter has been fully revised for current science and now features learning objectives and chapter summaries, supplemental reading, and 5 clinical case based multiple choice questions. New clinical cases have been added throughout."